2018
DOI: 10.1111/joop.12200
|View full text |Cite
|
Sign up to set email alerts
|

Being mindful at work and at home: Buffering effects in the stressor–detachment model

Abstract: In this daily diary study, we examined the moderating role of employee domain‐specific mindfulness within the stressor–detachment model (Sonnentag & Fritz, , Journal of Organizational Behavior, 36, 72). According to the stressor–detachment model, emotional and quantitative demands should be associated with decreased psychological detachment after work, which in turn is associated with decreased well‐being (i.e., low positive affect and high negative affect) at bedtime. Moreover, we proposed that both mindfulne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 69 publications
(124 reference statements)
9
65
0
1
Order By: Relevance
“…However, it seems that findings regarding the association between specific job stressors and detachment stemming from diary studies differ from cross-sectional findings (Sonnentag, 2018). In diary research and consistent with our findings, some stressors predict psychological detachment (e.g., self-control demands; Germeys & De Gieter, 2018), whereas some stressors do not-or at least not linearly (e.g., time pressure; Haun, Nübold, & Bauer, 2018).…”
Section: The Mediating Process In the Sd Modelsupporting
confidence: 68%
“…However, it seems that findings regarding the association between specific job stressors and detachment stemming from diary studies differ from cross-sectional findings (Sonnentag, 2018). In diary research and consistent with our findings, some stressors predict psychological detachment (e.g., self-control demands; Germeys & De Gieter, 2018), whereas some stressors do not-or at least not linearly (e.g., time pressure; Haun, Nübold, & Bauer, 2018).…”
Section: The Mediating Process In the Sd Modelsupporting
confidence: 68%
“…For instance, when subordinates experience low job involvement they might be less affected by their leaders' level of psychological detachment from work. Moreover, subordinate mindfulness might play a role as well (Haun, Nübold, & Bauer, 2018). When subordinates are highly mindful they might find it more easy to detach from work during nonwork time, even when their leaders stay mentally connected to work.…”
Section: Discussionmentioning
confidence: 99%
“…Valuable or instrumental personal characteristics include mindfulness, as it can be a coping skill for employees to deal with stressors at work (Jacobs & Blustein, 2008). Indeed, several studies have examined positive effects of mindfulness on occupational health among workers (i.e., Haun, Nübold, & Bauer, 2018; Hülsheger, Alberts, Feinholdt, & Lang, 2013). For example, mindfulness reduced negative career thoughts (Galles, Lenz, Peterson, & Sampson, 2019).…”
Section: Mindfulness As a Moderatormentioning
confidence: 99%
“…This tendency may make mindful individuals evaluate role conflict as less harmful than their counterparts because they try to view situations evincing role conflict nonjudgmentally and objectively. Reinterpretation of the situation (Shapiro et al, 2006) may permit workers to avoid the development of negative emotions by detaching themselves from the situation (Haun et al, 2018). Indeed, Long and Christian (2015) found that mindfulness reduced the effect of injustice on negative emotion.…”
Section: Mindfulness As a Moderatormentioning
confidence: 99%